ISSUES OF IMPROVING PROSECUTOR'S SUPERVISION OVER THE ORGANIZATION AND IMPLEMENTATION OF ELECTRONIC STATE PROCUREMENT REGARDING DESIGNATION OF PROJECTRESEARCH ORGANIZATIONS IN THE FIELD OF CONSTRUCTION. - Muxiddinov Abduraxim Akramjon o‘g‘li. (Scholar Express Journal, 2024)
According to the decree of the Cabinet of Ministers of the Republic of Uzbekistan dated 09.11.2020 No. 699, the implementation of the procedure for calculating and maintaining the rating of Project - Search and construction-contracting organizations is established. This decision included the procedure for forming and maintaining the rating data of legal entities registered on the territory of the Republic of Uzbekistan and whose main activity consists in the implementation of construction and installation works and services, as well as the corresponding license for the development of urban planning documents. The ratings provide the basis for the formation of a healthy competitive environment between project-search organizations, the promotion of increasing the level and quality of their innovative activities, the effective use of the potential of employees, the quality of construction and installation and project work for the real sector of the economy to the level in the world's leading countries by sector.
Keywords: leading; entities; organizations; healthy